Suppression of ERECTA Signaling Impacts Agronomic Performance of Soybean (Glycine max (L) Merril) in the Greenhouse - Berchembrock, Yasmin Vasques; Botelho, Flávia Barbosa Silva; Srivastava, Vibha (Frontiers in Plant Science, 2021)
The ERECTA (ER) family of genes, encoding leucine-rich repeat receptor-like kinase, influences complex morphological and physiological aspects of plants. Modulation of ER signaling leads to abiotic stress tolerance in diverse plant species. However, whether the gain in stress tolerance is accompanied with desirable agronomic performance is not clearly known. In this study, soybean plants potentially suppressed in ER signaling were evaluated for the phenotypic performance and drought response in the greenhouse. These plants expressed a dominant-negative Arabidopsis thaliana ER called ΔKinase to suppress ER signaling, which has previously been linked with the tolerance to water deficit, a major limiting factor for plant growth and development, directly compromising agricultural production. With the aim to select agronomically superior plants as stress tolerant lines, transgenic soybean plants were subjected to phenotypic selection and subsequently to water stress analysis. This study found a strong inverse correlation of ΔKinase expression with the agronomic performance of soybean plants, indicating detrimental effects of expressing ΔKinase that presumably led to the suppression of ER signaling. Two lines were identified that showed favorable agronomic traits and expression of ΔKinase gene, although lower levels compared to the rest of the transgenic lines. The drought stress analysis on the progenies of these lines, however, showed that these plants were more susceptible to water deficit stress as compared to the non-transgenic controls. The selected transgenic plants showed greater stomata density and conductance, which potentially led to higher biomass, and consequently more water demand and greater susceptibility to the periods of water withholding.